Politik Hukum Ratifikasi Konvensi PBB Anti Korupsi di Indonesia - Atep Abdurofiq (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstact : This study sought to see an international legal ratification of UN conventions in the form of anti-corruption and its impact on the internal environment of a country, especially Indonesia.Corruption is a never-ending problem discussed and resolved. Corruption became the nation's disease because it has been longstanding, massive and systemic. Corruptions become a disaster for the national economy and undermine system of governance. Corruption is not merely the loss of state money, but the impact on poverty and the miserable life of the people. Indonesia considers the UN anti-corruption convention is quite important in the effort to uphold the